Correlation of eosinophilic infiltration with the level of tumor invasion and metastasis into regional lymph nodes in rectal cancer - Pospishil, Yu. O.; Feshchur, H.R. (Pathologia, 2013)
Analysis of 220 specimens of surgical material from patients with rectal cancer in Lviv Cancer Center from 2002 till 2011 was done. With the increased level of tumor invasion the incidence of eosinophils in inflammatory cell peritumor infiltration reduced and incidence of metastases in regional lymph nodes increased.